The Fire - Neville, Katherine (New York Ballantine Books, 2009)
2003, Colorado: Alexandra Solarin is summoned home to her family's ancestral Rocky Mountain hideaway for her mother's birthday. Thirty years ago, her parents, Cat Velis and Alexander Solarin, believed that they had scattered the pieces of the Montglane Service around the world, burying with them the secrets of the power that comes with possessing it. But Alexandra arrives to find that her mother is missing and that a series of strategically placed clues, followed swiftly by the unexpected arrival of a mysterious assortment of houseguests, indicates that something sinister is afoot. 1822, Albania: Thirty years after the French Revolution, when the chess service was unearthed, all of Europe hovers on the brink of the War of Greek Independence. Ali Pasha, the most powerful ruler in the Ottoman Empire, has angered the sultan and is about to be attacked by Turkish forces. Now he sends the only person he can rely upon-his young daughter, Haidee--on a dangerous mission to smuggle a valuable relic out of Albania, through the mountains and over the sea, to the hands of the one man who might be able to save it
Sequel to: Eight, 1989
Keywords: Chess sets -- Fiction; Family secrets -- Fiction; Puzzles -- Fiction; Quests (Expeditions) -- Fiction